2022
DOI: 10.1002/ange.202113937
|View full text |Cite
|
Sign up to set email alerts
|

A Membrane‐Permeable and Immobilized Metal Affinity Chromatography (IMAC) Enrichable Cross‐Linking Reagent to Advance In Vivo Cross‐Linking Mass Spectrometry

Abstract: Cross-linking mass spectrometry (XL-MS) is an attractive method for the proteome-wide characterization of protein structures and interactions. Currently, the depth of in vivo XL-MS studies is lagging behind the established applications to cell lysates, because cross-linking reagents that can penetrate intact cells and strategies to enrich cross-linked peptides lack efficiency. To tackle these limitations, we have developed a phosphonate-containing cross-linker, tBu-PhoX, that efficiently permeates various biol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…We recently described a sample processing workflow, in particular a two-step Immobilized Metal Affinity Chromatography (IMAC) enrichment strategy for interactome profiling of intact cells based on the enrichable cross-linker tert -butyl-PhoX (tBu-PhoX) 17 . In this study, we further augment the tBu-PhoX XL-MS pipeline from the data acquisition perspective by integrating RTLS to advance cross-link detection.…”
Section: Introductionmentioning
confidence: 99%
“…We recently described a sample processing workflow, in particular a two-step Immobilized Metal Affinity Chromatography (IMAC) enrichment strategy for interactome profiling of intact cells based on the enrichable cross-linker tert -butyl-PhoX (tBu-PhoX) 17 . In this study, we further augment the tBu-PhoX XL-MS pipeline from the data acquisition perspective by integrating RTLS to advance cross-link detection.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, subsequent cellular and animal experiments can be conducted to understand whether such an interaction is functionally important in physiological conditions. Although some researchers have developed in vivo cross-linking probes to directly cross-link at the cellular level and identify protein interactions closer to physiological conditions, they also have the problems at the expense of the number of interprotein cross-links in low-abundance subcellular compartments (Figure S6). APEX-CXMS may be complementary to the in vivo cross-linking.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, CLASP can readily provide detailed localization predictions for any purifiable organelles but would likely be less powerful when applied to intact cells, since proteome coverage of most in-cell XL-MS workflows is currently still limited. However, with recent technological advancements of XL-MS, identification of tens of thousands of cross-links in intact cells is in reach (Jiang et al ., 2021; Wheat et al ., 2021) and CLASP paves the way to use these data for elucidating protein localizations across the cell.…”
Section: Discussionmentioning
confidence: 99%
“…4 nm and currently limited to cell surface proteins (Geri et al , 2020)). However, even though we and others have developed methods for proteome-wide XL-MS (Liu & Heck, 2015; Mendes et al , 2019; O’Reilly & Rappsilber, 2018) and have shown that these approaches can capture large parts of the proteome in intact cells and organelles (Fasci et al , 2018; Gonzalez-Lozano et al , 2020; Jiang et al , 2021; Liu et al , 2018; Schweppe et al , 2017; Wheat et al , 2021; Wittig et al , 2021), cross-linking has so far only been used to analyze protein structures and interactions.…”
Section: Introductionmentioning
confidence: 99%